- #1

- 144

- 0

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter veronicak5678
- Start date

- #1

- 144

- 0

- #2

AlephZero

Science Advisor

Homework Helper

- 6,994

- 293

The polynomial A(x-a)(x-b) is zero when x = a and x = b, and you can make it have any value you want at a third point x = c by choosing the value of A

So write the polynomial in the form

y = A(x-x2)(x-x3) + B(x-x0)(x-x3) + C(x-x0)(x-x2)

If you evaluate it at x = x0, you get

y0 = A(x0-x2)(x0-x3)

which gives you the value of A, and similarly for B and C.

- #3

- 144

- 0

Thank you!

Share:

- Replies
- 6

- Views
- 3K